Injectable Hydrogel as a Unique Platform for Antitumor Therapy Targeting Immunosuppressive Tumor Microenvironment - Liu, Yushuai; Geng, Yuanyuan; Yue, Beilei; Lo, Pui-Chi; Huang, Jing; Jin, Honglin (Frontiers in Immunology, 2022)
Cancer immunotherapy can boost the immune response of patients to eliminate tumor cells and suppress tumor metastasis and recurrence. However, immunotherapy resistance and the occurrence of severe immune-related adverse effects are clinical challenges that remain to be addressed. The tumor microenvironment plays a crucial role in the therapeutic efficacy of cancer immunotherapy. Injectable hydrogels have emerged as powerful drug delivery platforms offering good biocompatibility and biodegradability, minimal invasion, convenient synthesis, versatility, high drug-loading capacity, controlled drug release, and low toxicity. In this review, we summarize the application of injectable hydrogels as a unique platform for targeting the immunosuppressive tumor microenvironment.